Visualizing Spirituality as Character Education in Indonesian Grade 4 ELT Textbook - Ni Made Rini Antari; Luh Putu Artini; Luh Indrayani (Universitas Pahlawan Tuanku Tambusai, 2026)
This study investigates the presentation of spirituality as a character education value in the Grade 4 ELT students’ book entitled “My Next Word.” Employing a qualitative content analysis design, the research analyses and examines visual artifacts presented in the student’s book based on five subdimensions of spirituality, based on the dimension of faith in God Almighty of Graduate Profile Values framework. These subdimensions include spirituality in religious practice, spirituality in personal morality, spirituality in social morality, spirituality in environmental morality, and spirituality in civic morality. The findings reveal that spirituality in personal morality is the most frequently represented value in the book, reflected in visuals that emphasize discipline, cleanliness, responsibility, and self-care. This is followed by spirituality in social morality, which is evident in depictions of cooperation, respect, and helping behaviour. However, spirituality in religious practices, environmental, and civic moralities appears minimally and is not consistently highlighted throughout the book. Overall, these results indicated that the book integrated spirituality-based character education mainly through daily-life activities rather than explicit religious symbols or direct doctrinal representations, suggesting an implicit and practiced-oriented approach.